The task of prognostication main indicators of air company - D. Yu. Potapova (Омский научный вестник)
The issue of improving the efficiency of the functioning of airlines in the air transportation market is considered. A statistical and mathematical model has been developed and allows us to make a prognosis of the main indicators of the airline’s activity. This model is a distribution of a random variable, which distribution density is described by the Gauss’ Law. The influence of the correlation coefficient value on the accuracy of the prognosis, the average quadratic values on the mathematical expectation of the predicted value is shown. The given model allows to increase the accuracy of the prognosis of the indicators of the airline work.